Changes in the values of some blood elements in Shami goats and their relationship to hemoglobin genotypes (Journal of Hama University, 2022)
This research was conducted on 54 goats of the Shami goat genealogy at the Agricultural Scientific Research Station. The amount of the following blood elements (cholesterol, triglycerides, total protein, globulins and calcium ions) were studied and their proportions in the blood of goats were analyzed. The hemoglobin analogy on the gel were analyzed and their association with the hemoglobin genotypes AA, AB, and BB was determined using the starchy gel electrophoresis device, and the results were statistically analyzed.The results showed:The lowest value of cholesterol was 61 mg/dl at the BB formula, and the highest value was 63 mg/dl at the AA formula.Triglycerides had the lowest value of 15.8 mg/dl in the AB formulation, and the highest value was 18.9 mg/dl in the BB formulation.The highest value for total protein was 7 g/dl for the AA structure, and the lowest value for the protein was 6.7 g/dl for the AB structure.The highest value of globulin in the BB formulation was 4.4 g/dl and the lowest value was 4 g/dl in the AB formulation.Calcium ions showed that the highest value was 4.63 mEg/l at genotype BB, while the lowest value for calcium ions was 4.56 mEg/l at genotype AB.